Emotional Branding as an Effort to Improve the Quality of Library Service in Order to Increase the Use of Library - Komariah, Neneng; Rodiah, Saleha; Saepudin, Encang (Record and Library Journal, 2016)
This paper is a study of implementation of emotional branding in library services.Â Â Â  Emotional branding is a new paradigm in marketing world. It means create emotional nuance and its objective is to create an emotional nearness between a brand and its consumer. The library as an institution which provide information services may implement emotional branding concept in creating emotional nuance which will build emotional nearness between the library and its users. It is hope that the emotional nearnessÂ  will create usersâ satisfaction andÂ  loyality, so the use of library willÂ  increase. Emotional branding in library can be created through working performance of librarian who always try to create and maintain good relationships with users. Some strategies could be implemented, those are always ask the user first, ask their name and try to remember it, know information which usually needed, tell them when there is new information which relevant for them, create a situation that librarian always ready to help, show them that the librarian like to discuss with them, be a good listener, the librarian should be wear uniform with name tag, and be a mobile staff and ask the user if they need some helps.Â  The implementation of emotional branding in library services need a crucial change in mindset of library management in order to provide qualified services which suitable with usersâ demand.Â  Â